Students Today, Teachers Tomorrow? Identifying Constraints on the Provision of Education - Andrabi, Tahir; Das, Jishnu; Khwaja, Asim Ijaz (2012)
With an estimated 115 million children not attending primary school in the developing world, increasing access to education is critical. Resource constraints limit the effectiveness of demand-based subsidies. This paper focuses on the importance of a supply-side factor -- the availability of low-cost teachers -- and the resulting ability of the market to offer affordable education. The authors first show that private schools are three times more likely to emerge in villages with government girls' secondary schools (GSS). Identification is obtained by using official school construction guidelines as an instrument for the presence of GSS. In contrast, there is little or no relationship between the presence of a private school and girls' primary or boys' primary and secondary government schools. In support of a supply-channel, the authors then show that, for villages that received a GSS, there are over twice as many educated women and that private school teachers' wages are 27 percent lower in these villages. In an environment with poor female education and low mobility, GSS substantially increase the local supply of skilled women lowering wages locally and allowing the market to offer affordable education. These findings highlight the prominent role of women as teachers in facilitating educational access and resonate with similar historical evidence from developed economies. The students of today are the teachers of tomorrow.